Appraising the transformation and future of digital multisided platforms- A bibliometric analysis and systematic literature review - Qureshi, Farrukh Naseem; Pundziene, Asta; Adams, Richard (Institute of Electrical and Electronics Engineers (IEEE), 2024)
This article draws on the digital multisided platform (DMSP) literature from 1990 to 2022 to systematically review and synthesize its themes and contexts. We analyzed 344 articles from Web of Science and Scopus databases using a two-step approach: 1) bibliometric analysis to identify principle research themes in the DMSP literature; and 2) content analysis to develop these themes further. This article contributes to highlighting the DMSP role in Industry 4.0 and Service 4.0, which is an exclusive finding that has not been discussed by any other SLR paper before, along with highlighting competition and collaborative innovation, antitrust, platform typologies, and data privacy as a future research direction, also, this article analyzes the challenges and makes recommendations. In this way, the review advances the current understanding of the growing field of DMSP. Further, the article offers practical insights to guide policymakers, strategists, and managers about the prominent implications. The article does not only review the literature but offers a consolidated account of critical analysis, reviewing the evolution of DMSP. The bibliometric analysis depicts current research trends presenting us with four clusters: 1) innovation and entrepreneurship, 2) sharing economy, 3) business model, and 4) network effects in DMSP literature. We have identified research gaps and presented future research questions for scholars to investigate along with managerial implications of DMSP owners and stakeholders.
Keywords: Bibliometric analysis; digital multisided platform (DMSP); strategic management; systematic literature review (SLR); technology and innovation